Analysis of Class Teacher Social Competence (Study of Communication with Students, Peers, and Society)at SDI No 167 Mattoanging District of Turatea Jeneponto Regency - Wahyu Kamal; Andi Dewi Riang Tati; Muhammad Irfan (Program Studi PGSD FIP UNM, 2021)
The teachers are the factor that most determines the qualities of education, so the teachers required to have the potential to develop professionalism as a teacher. But there are still many teachers who are not able to develop their social competences. Research focus in this study are (1) How do the teachers understanding of social competence in the communication aspect in SDI No. 167 Mattoanging? (2) Do teachers in SDI No. 167 Mattoanging communicate affectively to students, professional friends (fellow teachers), and parents of students. This study aims (a) To find out an overview of the understanding of social competence of classroom teachers in SDI No. 167 Mattoanging on the aspects of communication. (b) To find out teacher communication with the students, fellow educators, education staff and parents of the students. The type of research is a descriptive approach through a qualitative approach. The sources used in this study were the principal as the key informant, teacher, education staff, parents of the students, the school committee as informant. Datum collected through observation, interviews, and documentation. Datum analyzed through the stages of data reduction, data presentation, data validity checks. The results of the study show that (1) the teachers do understand every aspect of social interaction of competences (2) the teachers’ communication is not affective in terms of each social component.